Literatur Review: Peran konseling gizi dan senam ergonomik dalam menurunkan kadar asam urat pada penderita gout - Nila Susanti; Yosi Sri Astuti; Harlyanti Muthma'innah Mashar (AcTion: Aceh Nutrition Journal, 2022)
Gout is a disorder caused by inflammation of the joints due to the deposition of uric acid crystals stored in the joints. The causative factors are age, excessive purine intake, obesity, alcoholic beverages, and lack of physical activity. Various efforts can be made to overcome this, including nutritional counseling and physical activity, such as gymnastics. The study aims to provide descriptive information regarding the effect of nutritional counseling on a low-purine diet and ergonomic gymnastics in reducing uric acid levels in patients with gout. Literature review research was conducted using the keywords "Counseling, Ergonomic Exercise, Uric acid, and Gout" on the Google Scholar search engine and other electronic databases, namely Proquest, BMC, and Cochrane review. Scientific articles are published in national and international journals that can be accessed openly, published between 2010-2020. From these results, 13 articles were selected for review. The literature review was conducted in an unsystematic narrative review. The results of the study state that providing counseling using various media can be one solution to help reduce pain and reduce one's uric acid levels, namely through counseling or nutrition counseling and ergonomic exercises. Counseling can provide insight or knowledge related to a low-purine diet, while ergonomic exercises provide the impact of physical fitness on the patient's health. The combination of providing nutritional counseling and ergonomic exercises can reduce uric acid levels in patients with gout.